Coming of age with HIV: a temporal understanding of young women's experiences in Zambia. Issue 2 (1st February 2021) - Mackworth-Young, Constance R. S.; Bond, Virginia; Stangl, Anne L.; Chonta, Mutale; Wringe, Alison
ABSTRACT: Young perinatally-infected women living with HIV in Zambia grew up alongside antiretroviral therapy (ART) roll-out and expanding prevention programmes. We used Bonnington's temporal framework to understand how HIV impacted the experiences of these women over time. Data were drawn from two sequential studies with a cohort of young women living with HIV: a qualitative study in 2014–16 and an ethnographic study in 2017–18. Data from workshops, in-depth interviews, participant observation and diaries were analysed thematically, guided by three temporalities within the framework: everyday, biographical and epochal time. In everyday time, repetitive daily treatment-taking reminded young women of their HIV status, affecting relationships and leading to secrecy with ART. In biographical time, past events including HIV disclosure, experiences of illness, and loss shaped present experiences and future aspirations. Lastly, in epochal time, the women's HIV infection and their survival were intimately interlinked with the history of ART availability. The epochal temporal understanding leads us to extend Reynolds Whyte's notion of "biogeneration" to conceptualise these women, whose experiences of living with HIV are enmeshed with their biosocial environment. Support groups for young women living with HIV should help them to process biographical events, as well as supporting their everyday needs.